You’re so Vain You Probably Think this Keynote is about You: Expanding Art and Music in Criminal Justice - Payne, Brian K. (American journal of criminal justice, 2012)
Criminal justice has long been recognized as an interdisciplinary field of study. When cross disciplines are considered, attention is often given to closely related social science disciplines such as sociology and political science. A closer look, however, reveals that criminal justice overlaps with numerous arts-oriented disciplines including art and music. This article highlights the overlap between criminal justice and these disciplines and makes a case for greater collaboration between these disciplines. Barriers to cross-disciplinary work are addressed along with strategies to promote collaboration.